Pengaruh Komunikasi Interpersonal Orang Tua terhadap Peningkatan Prestasi Belajar Anak di SMA Katolik Mariana Medan - Niscaya Hia; Eva Margareth Sarah; Magdalena Naibaho (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
Interpersonal communication in the family involves communication between parents and children. Parents have a responsibility and an important role in the learning process that excels and guides children. To improve children's learning achievements, they need parental support. Even though they are busy, the relationship between parents and children must be open to each other to share every activity that is carried out. This study aims to determine the extent of the influence of parent-child interpersonal communication in improving children's learning achievement at Mariana Catholic High School Medan. The type of research used is quantitative research with a correlational study approach. The population in this study is all parents of Mariana Catholic High School students in Medan, and the sample in this study amounted to 55 parents of students using the Yamane formula using a purposive sampling technique. Data collection techniques in this study used documentation and questionnaires distributed to respondents and data analysis techniques using Product Moment Correlation. This study resulted in a significant relationship between interpersonal communication and learning achievement with evidence that the value of 5.479 (>) was greater than the value of 1.674, which means Ho is rejected and Ha is accepted with a significance value of 0.000 0.05. So it can be concluded that there is a strong level of relationship between variable X and variable Y from the correlation results calculated using the SPSS version 25 program, namely 0.601, which is at the level of a strong correlation interval, namely (0.60–0.799), so that from the calculation of data analysis there is the influence of parental interpersonal communication on improving children's learning achievement at Mariana Catholic High School Medan. Interpersonal communication and learning achievement are key terms.